Game Changer: Impact of a Reading Intervention on Cognitive and Non-cognitive Skills - Micole De Vera; Javier Garcia-Brazales; Luz Rello (Institute of Labor Economics (IZA), 2024)
We evaluate a reading intervention involving 600 third-grade students in Chilean schools catering to disadvantaged populations. The intervention features an adaptive computer game designed to identify and improve weaknesses in literacy and cognitive skills, and is complemented by a mobile library and advice to parents to increase student's interest and parental involvement. We first quantify the impact on non-cognitive skills and academic perceptions. We find that, after just three months of intervention, treated students are 20–30 percent of a standard deviation more likely to believe that their performance is better than that of their peers, to like school, to have stronger grit, and to have a more internal locus-of-control. Gains in aspirations and self-confidence are particularly large for students that we identify as at-risk-of-dyslexia. These improvements are reflected in better performance on a nation-wide, standardized language test. Our results show that non-cognitive skills, particularly of at-risk-of-dyslexia students, can be changed through a short, light-touch, and cost-effective education technology intervention.
Keywords: I24; I31; 330; field experiment; computer-based reading intervention; non-cognitive skills; Chile; dyslexia